MEMPREDIKSI KURS SPOT DI MASA DEPAN DENGAN KURS FORWARD - Dewa Putra Krishna Mahardika (Faculty of Economic and Business, University of Pasundan, 2018)
Since the fall of Bretton Woods in 1970s forex market entered market-determined regime, several theories have been developed by academicians and practitioners to help predicting the movement of future spot rate in forex market. One of those theories is Forward Rate as Unbiased Predictor (FRUP). Basically FRUP predicts movement on future spot rate based on current forward rate. If FRUP is valid, then predicting future spot rate can be determined only by looking at current forward rate. This paper tests the validity of FRUP on USD/IDR rate. USD/IDR forward rate with tenor 1-, 3-, 6- and 12-month will be used to predict USD/IDR spot rate 1-, 3-, 6- and 12-month on the future. To test the validity of FRUP, linear regression will be used to measure the correlation between spot rate and forward rate. The result shows that current forward rate is a poor predictor of future spot rate.